Pengembangan Even Budaya Di Kelurahan Ledok - Nina Mistriani; Nurdina Prasetya; Yudi Mochamad Ariyanto (Community : Jurnal Pengabdian Pada Masyarakat, 2021)
The growth of the mainstay area in Central Java is expected to be able to provide a positive break-even for the economic growth of the surrounding area or the area behind it (hinterland), through civilizing the sector or sub-sector base as a driver of the regional economy and economic linkages between regions. The main objective of the mainstay area is to accelerate development. The city of Salatiga which is the goal of this service and research based on its location has a strategic location.